Hydrophobization of dense and fine concrete by polysulfide solutions - MASSALIMOV Ismail Alexandrovich; YANAKHMETOV Marat Rafisovich; CHUYKIN Aleksandr Evgenievich; MASSALIMOV Burhan Ismailovich; URAKAEV Farit Hisamutdinovich; URALBEKOV Bolat Muratovich; BURKITBAEV Muhambetkali Myrzabaevich (Нанотехнологии в строительстве, 2016)
The results of research on hydrophobic impregnation of dense concrete with composition «Aquastat» designed for manufacture of road and airfield plates are presented. It was found that after having been treated with waterrepellent agent the concrete sample is resistant to wetting, i.e. it gets hydrophobic properties. At the same time the water absorption of the samples treated for 24 hours at atmospheric pressure is reduced in three times, and soaked for 0.5 hours under vacuum decreases 5.5 times. It was revealed that the hydrophobic properties of fine-grained concrete impregnated with «Aquastat» may be at the same level of those of dense concrete based on coarse filler. Substantially increased hydrophobic properties of dense concrete (more than 5 times) allow authors to forecast twice increased service life of road and airfield plates treated by «Aquastat» composition.